2008
DOI: 10.1016/j.tet.2007.12.006
|View full text |Cite
|
Sign up to set email alerts
|

An efficient enzymatic preparation of 20-pregnane succinates: chemoenzymatic synthesis of 20β-hemisuccinyloxy-5αH-pregnan-3-one

Abstract: This article was published in an Elsevier journal. The attached copy is furnished to the author for non-commercial research and education use, including for instruction at the author's institution, sharing with colleagues and providing to institution administration. Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors are permitted to post their version of the article (e.g. in Wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Alkaline hydrolysis of 7 liberated 7a, having 1 H NMR and EIMS data consistent with those of 20-hydroxypregn-4-en-3-one. 9 This revealed that 7 was 20-Omyristoylpregn-4-en-3-one, which was confirmed by the HMBC correlations of H 3 -21/C-17 and C-20 and H-20/C-1′. The ECD spectrum of 7 showed Cotton effects at 235 (Δε +5.78) and 322 (Δε −1.21) nm, corresponding to the π→π* and n→π* transitions of the conjugated 4-en-3-one chromophore, indicating that the tetracyclic nucleus of 7 possessed the same absolute configuration as the common pregn-4-en-3-one analogues on the basis of the octant rule.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkaline hydrolysis of 7 liberated 7a, having 1 H NMR and EIMS data consistent with those of 20-hydroxypregn-4-en-3-one. 9 This revealed that 7 was 20-Omyristoylpregn-4-en-3-one, which was confirmed by the HMBC correlations of H 3 -21/C-17 and C-20 and H-20/C-1′. The ECD spectrum of 7 showed Cotton effects at 235 (Δε +5.78) and 322 (Δε −1.21) nm, corresponding to the π→π* and n→π* transitions of the conjugated 4-en-3-one chromophore, indicating that the tetracyclic nucleus of 7 possessed the same absolute configuration as the common pregn-4-en-3-one analogues on the basis of the octant rule.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…F 3-6 (1.6 g) was repeatedly separated by CC over silica gel (petroleum ether−EtOAc, 50:1−3:1), followed by RP semipreparative HPLC (94% MeOH in H 2 O) purification to yield (E)-4-oxo-β-dihydroionone (1.8 mg), (3S,5R,6S)-3-acetoxy-5,6-epoxy-5,6-dihydro-β-ionone (1.5 mg), (22E)-ergosta- 6,9,22-triene-3β,5α,8α-triol (3.6 mg), and (22E)-ergosta-6,22-diene-3β,5α,8α-triol (5.0 mg). F 6 (21.0 g) was separated by flash chromatography over MCI gel, to give F 6-1 −F [6][7][8][9][10][11] . Separation of F 6-7 (3.6 g) by chromatography over Sephadex LH-20 (petroleum ether−CHCl 3 −MeOH, 2:2:1) and RP semipreparative HPLC (60% MeOH in H 2 O) yielded 1 (31.9 mg), 2 (1.8 mg), 3 (2.0 mg), 4 (4.1 mg), and 5 (3.4 mg).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, in previous papers, we observed that, in androstanes and pregnanes, Candida rugosa lipase showed a preference for C‐3‐hydroxy or ‐acyloxy groups, whereas Candida antarctica catalyzed the reactions at the D‐ring 22. Taking into account these properties, we have prepared fatty acid derivatives of dehydroepiandrosterone,23 3,17‐β‐estradiol,24 and a series of novel 20‐succinates of pregnanes 25…”
Section: Introductionmentioning
confidence: 91%
“…[21][22][23][24][25]. In our laboratory several studies have been accomplished on the use of lipases, obtaining a wide variety of biologically active compounds, many of them new [26][27][28][29][30][31][32][33][34][35].…”
Section: Scheme 1 Structure Of Important Bile Acidsmentioning
confidence: 99%